ChemInform Abstract: An in situ Directing Group Strategy for Chiral Anion Phase‐Transfer Fluorination of Allylic Alcohols. Issue 13 (March 2015) - Zi, Weiwei; Wang, Yi‐Ming; Toste, F. Dean
Abstract The enantioselective fluorination of allylic alcohols relies on an in situ generated directing group which is crucial for achieving effective enantiocontrol.